Faktor-Faktor Yang Mempengaruhi Rasio Keuangan Sebagai Prediktor Dari Kinerja Keuangan Perusahaan - Ringke Dirdia; Deci Novesa Carani; Henny Setyo Lestari (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study aims to examine the impact of the quick ratio, total assets turnover, leverage, company size, sales growth, and the consumer price index on the financial performance of companies in the property and real estate sub-sector manufacturing companies listed on the Indonesia Stock Exchange during the 2016-2020 period. a total of 39 companies. The sampling technique was the purposive sampling method. Data analysis using Eviews 10 software. The regression analysis technique is used to more on the influence of financial factors on the company's financial performance, as a result, it can be relied upon to be the basis for conveying suggestions. The results of the analysis share that total assets turnover, leverage, sales growth, and the consumer price index have an impact on financial performance as measured by ROS and ROE. The quick ratio and company size have no effect on the financial performance of the property and real estate sub-sector manufacturing companies listed on the Indonesia Stock Exchange.